An alternative methodology addressing United Nations classification type for self‐reactive substances. Issue 1 (28th July 2022) - Raines, Elizabeth; Doup, Benjamin
Abstract: The UN "Recommendations on the Transport of Dangerous Goods" presents schemes for the classification of hazardous materials such as explosives, flammable liquids, or oxidizing substances, and gives descriptions of the test methods and procedures for the selection of appropriate packages and shipping types, as well as consignment procedures. Substances are classified according to their degree of danger, and the "Model Regulations" provide a hazard hierarchy. Class 4.1 and Class 5.2 materials are self‐reactive and solid desensitized explosives, and organic peroxides, respectively, and these hazard classes trump many other classification levels. The UN "Manual of Tests and Criteria" provides standard test methods for classifying self‐reactive and organic peroxide substances into seven groups (A–G) according to their hazard levels but also allows for other procedures to be used provided that adequate correlation has been obtained with the classification tests on a representative range of substances. There are eight test series (A–H) documented in the Manual of Tests and Criteria that could be needed in order to identify the hazard level for Class 4.1 and Class 5.2 materials, which can be an expensive and time‐consuming requirement. An alternative method aimed at streamlining the hazard classification process is proposed. This alternative method utilizes low phi‐factor adiabatic calorimetry data and the measured maximum rate of pressure rise to classify self‐reactive and organic peroxide substances for transport. Benchmarking experiments using this alternative method to classify t ‐butyl perbenzoate, 50%–70% TBHP in decane, and 70% TBHP in water are promising, indicating that further evaluation of the proposed method is warranted.